2009
DOI: 10.1016/j.jtcvs.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Tracking cardiac engraftment and distribution of implanted bone marrow cells: Comparing intra-aortic, intravenous, and intramyocardial delivery

Abstract: This is the first study to correlate live cell imaging with quantitative genetic and histologic techniques. Noninvasive molecular imaging tracked delivered cells and will permit the evaluation of new and improved delivery platforms designed to increase cell homing, retention, and engraftment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 25 publications
5
79
0
3
Order By: Relevance
“…Interestingly, this study also revealed the importance of the timing of delivery with regard to the ischemic event. When cells were injected into an acute infarct there was a 50% survival rate at 2 h, but improved retention was observed when cells were injected into a more mature infarct (15). These results confirm the critical need of a cell tracking technique in the early phase after delivery of therapeutic cells, which would be possible with our ICG-labeling technique.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, this study also revealed the importance of the timing of delivery with regard to the ischemic event. When cells were injected into an acute infarct there was a 50% survival rate at 2 h, but improved retention was observed when cells were injected into a more mature infarct (15). These results confirm the critical need of a cell tracking technique in the early phase after delivery of therapeutic cells, which would be possible with our ICG-labeling technique.…”
Section: Discussionsupporting
confidence: 72%
“…Promising results derived from preclinical and proofof-concept clinical trials using MSC for cardiac repair have shown their potential to alleviate the deleterious effects of myocardial ischemia [19,20], despite documented poor cell retention after cell injections [21,22]. To achieve widespread clinical application of cell-based therapies for post-ischemic heart failure, the selection of an optimal cell type combined with a therapeutically relevant timing, as well as a well optimized delivery method are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In order to track engraftment and distribution of transplanted MSCs, Li and colleagues delivered male rat MSCs into female rats via intraaortic, intravenous, and intramyocardial injections, either 3 or 28 days after a myocardial infarction was induced. 43 At 24 and 48 hours after implantation, a significantly greater number of MSCs was retained in the heart when delivered through direct intramyocardial injection, rather than through other delivery routes. 43 In a swine model, Shake et al…”
Section: In Vivo Studiesmentioning
confidence: 95%
“…43 At 24 and 48 hours after implantation, a significantly greater number of MSCs was retained in the heart when delivered through direct intramyocardial injection, rather than through other delivery routes. 43 In a swine model, Shake et al…”
Section: In Vivo Studiesmentioning
confidence: 95%